‘사회적기업 혁신체제’ 접근을 통한 사회적기업 연구경향 분석 - 강민정(Minjeong Kang) (한국비교정부학보, 2014)
This research explores how SE research trends are being configured in Korea and suggests new research agenda by using a framework of 'social enterprise innovation system'. For this, 173 papers in total are selected, which are published in journals registered at Korea Citation Index (KCI), dating from 2010 to October, 2013. The papers are classified based on 'Social Enterprise Innovation System' as an analytical framework, which consists of four main parts; Players' Goals and Purposes, Competing and Collaborating Constituents, Social Trends and Industrial Standards, Inter-organizational Governance. Based on the result of this analysis, this study suggests that researchers need to pay more attention to the field of 'Competing and Collaborating Constituents' and 'Inter-organizational Governance' with a particular attention to a wide range of case studies and interdisciplinary approaches. Research on this field also needs to contribute to value creation in social businesses, education and training of members in social enterprises, and creative ways of capitalizing on rich experiences of civil and cultural activities accumulated through Korea's modern history for establishing a sustainable growth strategy of social enterprises. KCI Citation Count: 13